(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2004)
This paper examines a number of theories of anxiety, beginning with the philosophical accounts of Kierkegaard and Heidegger, followed by an outline of Freud’s conceptualisation of anxiety. This is then contrasted with an exploration of how the philosophical accounts of anxiety have been interpreted and translated into theories of existential psychology. The focus here is mainly upon the work of Rollo May and Paul Tillich. And finally consideration is given to some of the more recent contributions to the understanding of anxiety and the implications for psychotherapy.